Geraghty’s Fixed Point Theorem for Partial-Special Multi-Valued Mappings: Vincenzo La Rosa - Team, Support (Thai Journal of Mathematics, 2018)
In this paper we recall the concept of partial Hausdorff metric. Many authors studied about fixed point theory for multi-valued mappings on a partial metric space using the partial Hausdorff metric. We prove a generalization of Geraghty's fixed point theorem for a type of multi-valued mapping that called partial-special multi-valued mapping in partial metric space.